Opór jako fenomen interdyscyplinarny – inspiracje dla pedagogiki specjalnej - GUMIENNY, BEATA (Interdyscyplinarne Konteksty Pedagogiki Specjalnej, 2018)
Beata Gumienny, Opór jako fenomen interdyscyplinarny – inspiracje dla pedagogiki specjalnej [Resistance as an interdisciplinary phenomenon – inspiration for special education]. Interdyscyplinarne Konteksty Pedagogiki Specjalnej, nr 22, Poznań 2018. Pp. 239-258. Adam Mickiewicz University Press. ISSN 2300-391X. DOI: https://doi.org/10.14746/ikps.2018.22.14 The article is concerned with the issue of resistance, with particular focus on the philosophical, sociological, psychological and educational adumbration. The interdisciplinary notion of the resistance phoneme constitutes a contribution to its introduction to the special education area, to the world of persons with disabilities. Moreover, attention was drawn to the learning environment as a place triggering the students’ resistance to the school system and authority. The undertaken considerations have been located in the critical theory, defining the stance on authoritarianism, injustice, emancipation or liberation, and especially on stigmatization, marginalization and exclusion.